The effects of economic austerity on pro-sociality: Evidence from Greece - Nicholas Sambanis; Elena Nikolova; Anna Schultz (Global Labor Organization (GLO), 2022)
The European sovereign debt crisis resulted in policies of fiscal austerity and economic downturn in Greece, marked by a prolonged period of recession and high unemployment. This article explores the social impact of the economic crisis, focusing on its effects on altruism using new household-level survey data and quasi-behavioral outcomes. We focus on the effects of joblessness, the most severe form of economic hardship imposed as a result of the crisis. Our findings reveal a strong relationship between job loss in the household and decreased altruism. We provide experimental evidence of these effects and of in-group bias in charitable giving as a result of joblessness. Our results show that joblessness intensifies survey respondents' preferences for national as opposed to foreign charities.
Keywords: D64; E64; C93; 330; Austerity; solidarity; altruism; joblessness